The influence of Ludwik Krasiński and Maria Ludwika Czartoryska on Ojców architecture at the turn of the 20th century and between the two world wars - Joanna Ziarkowska; Dominik Ziarkowski (Folia Historica Cracoviensia)
In the second half of the 19th century, a spa was set up in Ojców, a village at the time situated by the southern border of the Kingdom of Poland. With time, it became a fashionable destination for visitors from Warsaw, and from other towns and cities located in the territory of the Russian sector of partitioned Poland. Ojców experienced its heyday early in the 19th and 20th centuries and its spa activities continued also between the two world wars. The Ojców demesne was then owned by Count Ludwik Krasiński and his daughter Maria Ludwika, from 1901 Princess Czartoryska. The latter remained the owner of Ojców until the nationalisation of the estate in the wake of the agrarian reform of 1944.